Simulation the Beta Power Sources Characteristics - S.Yu. Yurchuk; S.A. Legotin; V.N. Murashev; A.A. Krasnov; Yu.K. Omel’chenko; Yu.V Osipov; S.I. Didenko; O.I. Rabinovich (Журнал нано- та електронної фізики)
In this paper the simulation of silicon beta-stimulated power sources spectral sensitivity characteristics was carried out. It was analyzed the influence of the semiconductor material characteristics (the doping level, lifetime) and power supply design on the photosensitive structures characteristics in order to optimize them.